Representation of Women Victims of Sexual Violence (Discourse Analysis of the Film “Like & Share”) - Setiawan, Yuda; Ramailis, Neri Widya (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
In recent years, many artists and feminists have transformed their struggles through artistic media such as film. The power and ability of film to reach diverse social segments make it an influential medium in shaping public opinion. Like & Share, directed by Gina S. Noer, is one such film that seeks to participate in constructing narratives about victims and their positioning by emphasizing certain information. This study aims to explore how victim representation is visualized in the film Like & Share by employing radical feminist perspectives and News Making Criminology. The research adopts a visual criminology approach using discourse analysis as its method. The findings reveal that Like & Share constructs a narrative that critiques the legal system and the patriarchal culture, which remain dominant as the root causes of women’s suffering as victims of sexual violence. The representation of women in this film illustrates the dynamic between oppression and resistance against patriarchal systems, emphasizing that women are still entrapped in injustice. Furthermore, the film conveys the idea that patriarchy continues to serve as the fundamental source of women’s subjugation by depicting various forms of oppression, including the objectification of women, the normalization of sexual violence, societal neglect toward victims, and a legal system that fails to support them.